Impact of Foot Placement on Muscle Activation and Weight Distribution During Sit-to-Stand in Chronic Stroke Patients - Salib Kamel, Marina Azmy; A Atteya, Abdulalim; Ibrahim, Wael; S. Ali, Ahmed (Journal of Neonatal Surgery, 2025)
Background: Comprehensive neurorehabilitation for post-stroke could improve physical capacity and reduce healthcare costs post-strokes. Effective execution of sit-to-stand is an important goal of neurological rehabilitation that requires appropriate lower limbs coordination. Purpose: The objective of this study was to investigate the changes in lower limb muscle activation patterns during the sit-to-stand movement, across three different initial foot placements: symmetric foot position, affected foot placed in front of the unaffected foot, and affected foot placed behind the unaffected foot. Surface electromyography (EMG) was used to assess muscle activity during these movements. Participants and Methods: Forty Egyptian chronic hemiparetic participants of both genders, their age range 45- 60 years old, duration of disease was > 6 months, their spasticity grade was mild range 1 to 1+, according to the Modified Ashworth scale, the patients were recruited from Outpatient clinic and Research laboratories at Faculty of Physical Therapy, Cairo University, Egypt, between May 2022 to May 2023. All demographic data, Tibialis Anterior and Rectus Femoris muscle activity were recorded using Surface EMGs (EMG-USB2) while performing sit-to-stand using three different positions for the foot placement, then statistical analysis was conducted. Results: The demographic data were consistent with globally recognized stroke-related factors. The anterior foot placement resulted in the highest activation of the tibialis anterior during sit-to-stand, as evidenced by its highest maximum amplitude and a "borderline significance" value for amplitude-to-frequency. Both the symmetric and anterior foot placements elicited the highest activation of the rectus femoris, indicated by their highest maximum amplitude. In contrast, the posterior foot placement showed the lowest rectus femoris activation, as evidenced by the lowest clustering index. Conclusion: The anterior foot placement is the most effective for activating the tibialis anterior, making it a critical strategy for enhancing dorsiflexor function. Additionally, both symmetric and anterior foot positions are particularly beneficial for optimizing rectus femoris activation during sit-to-stand movements in individuals with chronic stroke.